The Socket-Shield Technique: Digital Planning, Guided Surgery, and Immediate Implant Loading—2-Year Follow-Up - Sušić Mato; Smojver Igor; Stojić Luka; Katalinić Ivan; Gerbl Dražena; Vuletić Marko (Case Reports in Dentistry)
Anterior aesthetic zone implant placement and tooth restoration can be a quite challenging procedure. Modern technology offers new tools that can help maximize results in both aesthetic and functional ways. The socket-shield technique, as described by Hürzeler et al., boosted with the 3D diagnostics, digital planning, and 3D printing, could provide a valuable alternative to traditional approaches. This case report describes a clinical workflow for an efficient anterior implant-prosthetic restoration.